Synthesis, characterization and ionic conductivity of MgAl2O4 - Elmhamdi, Abdelhakim; Nahdi, Kais (European Journal of Chemistry, 2015)
Magnesium aluminate nanoparticles have been synthesized by a citrate sol-gel route. X-ray diffraction and IR spectroscopy study confirmed the formation of MgAl2O4 cubic spinel structure without presence of any secondary phase. Crystallite size of the synthesized nanoparticles was found to be equal to 24 nm. The ac conductivity of MgAl2O4 was studied using complex impedance spectroscopy technique in the frequency range from 5 Hz to 13 MHz and temperature range from 673 to 798 K. The temperature and frequency dependence of ac conductivity were highlighted and the activation energies of, respectively, ac conduction and relaxation processes were also calculated.